(3GdfhQ GdLdj aj GdfSH GdTQja GdfHhis - (3MSf Hf YHO Gddg Hf eMeO GdHNTj, CHh GdNdGU,J (B1190 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hCaVd GdUdGI hCJe GdJSdje Ydi SjOfG eMeO NGJe GdfHjjf s
(3BNQgG (B:s
(3j s
(3GdfSNI HgG MhGTs
(3hbO CJe GdeDda JCdjagG SfI (B1171(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B197 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B170 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs